Notebook by Florence O'Donoghue titled "Sources to read and check", - O'Donoghue, Florence, 1895-1967 (1947)
Notebook contains lists of books, articles and newspaper publications with notes taken from them, ink, pencil, and pink coloured pencil. Also includes a list of names with dates, possibly taken from monuments, and other notes scattered through the notebook.